The Epistemological Analysis About The Impact of Habitual Daily Journal Writing on Literacy Skills - Pranowo Lestari, Dyah; Asdlori (International Proceedings of Nusantara Raya, 2024)
Based on reflection and observation, the suboptimal literacy skills reflected in the Education Report are due to literacy activities that have not been systematically planned. This study discusses, from an epistemological perspective, the practice of writing daily journals as a habit to improve literacy, which can build knowledge and literacy skills in fourth-grade students in Phase B. Using a qualitative approach, this research analyzes best practices to understand the thinking process and comprehension of texts stimulated by questions. The instruments used, besides documents and practice analysis, also include digital literature reviews. The practice of habituating students to write daily journals focuses on understanding, experience, perception, and the writing process itself as a form of meaningful learning. The impact or outcome of this activity includes language skills, stimulating cognitive development, and supporting students in becoming more active, critical, and creative learners.